(untitled) (Global Journal of Science Frontier Research, 2020)
In this study one hundred and five (105) day old each of Cobb broilers and cockerel chicks in two separate studies were allocated to five treatments, 3 replicate per treatment and seven (7) birds per replicate in a complete randomize design. 1mls, 2mls, 3mls, and 4mls of the extract formulation of Ageratum conyzoides was administered per a liter of drinking water to treatment R1, R2, R3, and R4 and 1g/liter antibiotics for the control treatment respectively for three days in a week (Tuesday, Wednesday and Thursday) for five weeks. Broiler and cockerel growth performance and meat physical characteristics were evaluated. Data collected was subjected to analysis of variance (ANOVA) Duncan’s Multiple Range Test was computed to compare the difference among the treatment means at probability of 5%. The results revealed that there was no significant effect (P>0.05) on the growth performance of broiler and cockerel chicks except for TFI and FCR that performed better (P